Mittanische und mittelassyrische Keramik Eine chronologische, funktionale und produktionsökonomische Analyse - Pfälzner, Peter (Berichte der Ausgrabung Tall Šēḫ Ḥamad, Dūr-Katlimmu (BATSH), 1995)
Our knowledge of the Late Bronze Age utilitarian pottery of northern Mesopotamia has so far been based on a rather eclectic source material that did not offer anything approaching typological completeness and defied a more precise chronological classification. Moreover, the superficial impression hardly raised hope for improvement of the situation, since the material appeared rather stereotypical. This state of affairs, which was equivalent to a desideratum, is to be remedied with the present publication.